Immersible ergocycle prescription as a function of relative exercise intensity - Mauricio Garzon; Mathieu Gayda; Anil Nigam; Alain-Steve Comtois; Martin Juneau (Elsevier, 2017)
Purpose: The purpose of this study was to establish the relationship between various expressions of relative exercise intensity percentage of maximal oxygen uptake (%VO2max), percentage of maximal heart rate (%HRmax), %VO2 reserve (%VO2R), and %HR reserve (%HRR)) in order to obtain the more appropriate method for exercise intensity prescription when using an immersible ergocycle (IE) and to propose a prediction equation to estimate oxygen consumption (VO2) based on IE pedaling rate (rpm) for an individualized exercise training prescription. Methods: Thirty-three healthy participants performed incremental exercise tests on IE and dryland ergocycle (DE) at equal external power output (Pext). Exercise on IE began at 40 rpm and was increased by 10 rpm until exhaustion. Exercise on DE began with an initial load of 25 W and increased by 25 W/min until exhaustion. VO2 was measured with a portable gas analyzer (COSMED K4b2) during both incremental tests. On IE and DE, %VO2R, %HRmax, and %HRR at equal Pext did not differ (p > 0.05). Results: The %HRR vs. %VO2R regression for both IE and DE did not differ from the identity line %VO2R IE = 0.99 × HRR IE (%) + 0.01 (r2 = 0.91, SEE = 11%); %VO2R DE = 0.94 × HRR DE (%) + 0.01 (r2 = 0.94, SEE = 8%). Similar mean values for %HRmax, %VO2R, and %HRR at equal Pext were observed on IE and DE. Predicted VO2 obtained according to rpm on IE is represented by: VO2 (L/min) = 0.000542 × rpm2 − 0.026 × rpm + 0.739 (r = 0.91, SEE = 0.319 L/min). Conclusion: The %HRR-%VO2R relationship appears to be the most accurate for exercise training prescription on IE. This study offers new tools to better prescribe, control, and individualize exercise intensity on IE.